Characterisation of probiotic properties of yeast strains isolated from kefir samples - Goktas, Hamza; Dikmen, Hilal; Demirbas, Fatmanur; Sagdic, Osman; Dertli, Enes (WILEY, 2021)
This study aimed to isolate and identify yeast species from kefir samples and to determine their probiotic characteristics in comparison with commercial probiotic yeast Saccharomyces boulardii. The microbial flora of traditional kefir samples were dominated by Saccharomyces cerevisiae and Kluyveromyces marxianus. Kefir isolates demonstrated higher auto-aggregation, hydrophobicity and antioxidant properties compared to S. boulardii although S. boulardii demonstrated the highest survival rate under in vitro gastrointestinal digestion conditions followed by two kefir yeasts K. marxianus and Kazachstania unispora. Importantly, kefir isolates revealed strong antifungal activities against mould species except Penicillium roqueforti. These findings suggest probiotic and functional roles of yeast strains isolated from traditional kefir samples.
Keywords: Kefir; Probiotic; FT-IR; Saccharomyces; Hydrophobicity; Auto-aggregation; LACTIC-ACID BACTERIA; IN-VITRO CHARACTERIZATION; FUNCTIONAL-PROPERTIES; SOURDOUGH; Food Science & Technology